THE IMPACT OF GODDS ON POLITICAL POWER IN ANCIENT IRAQ - Mahmood, Hassan (Humanities Journal of University of Zakho, 2024)
This research, titled "The Impact of Godds on Political Power in Ancient Iraq," delves into the connection between religion and political authority in ancient Iraq. It explores how religion influenced kings and the political systems across different historical periods in ancient Iraq. The study highlights how rulers utilized religion to justify their authority, claiming divine endorsement to legitimize their political control over the civilization. The research is structured with an introduction, three sections, and a list of sources. The first section explores the role of religion, the second part delves into the significant gods in ancient Iraq, and the third section investigates how gods played a crucial role in shaping political power in this ancient civilization. The study concludes by presenting key findings.